Four New 2-(2-Phenylethyl)-4H-chromen-4-one Derivatives from the Resinous Wood of Aquilaria sinensis and Their Inhibitory Activities on Neutrophil Pro-Inflammatory Responses - Wang, Sin-Ling; Liao, Hsiang-Ruei; Cheng, Ming-Jen; Shu, Chih-Wen; Chen, Chun-Lin; Chung, Mei-Ing; Chen, Jih-Jung (Planta Medica, 2018)
Four new 2-(2-phenylethyl)-4H-chromen-4-one derivatives, 6-hydroxy-5-methoxy-2-[2-(4′-methoxyphenyl)ethyl]chromone (1), 6,7-dimethoxy-2-[2-(2′-hydroxyphenyl)ethyl]chromone (2), 5-hydroxy-6-methoxy-2-[2-(3′-methoxyphenyl)ethyl]-chromone (3), and 7-chloro-8-hydroxy-2-[2-(4′-methoxyphenyl)ethyl]chromone (4), have been isolated from the resinous wood of Aquilaria sinensis, together with 16 known compounds (5–20). Among these, 7-methoxy-2-[2-(4′-methoxyphenyl)ethyl]chromone (5) was isolated from a natural source for the first time. The structures of the new compounds were established by spectroscopic analyses (1D and 2D NMR, HR-ESI-MS, IR, UV). Nine compounds, including 1 showed more than 80% inhibition of superoxide anion generation by human neutrophils in response to formyl-L-methionyl-L-leucyl-L-phenylalanine at 50 µM.
Keywords: Aquilaria sinensis; Thymelaeaceae; resinous wood; 2-(2-phenylethyl)-4H-chromen-4-one; human neutrophils; anti-inflammatory activity